Familial perianal streptococcal dermatitis. - Patrizi, A.; Raone, B.; Gurioli, C.; Neri, I. (European Journal of Pediatric Dermatology, 2009)
Perianal Streptococcal Dermatitis (PSD) is a well known infection primarily affecting children. PSD is clinically characterized by a sharply demarcated erythematous patch and is most commonly caused by group A beta-hemolytic Streptococcus (GABHS). PSD usually occurs as an isolated dermatosis, however familial cases have been rarely described. Herein we report three brothers with a diagnosis of PSD with a herpes simplex-like presentation in one case.